BERINOVASI BERSAMA VERAFLOWER : ANALISIS SWOT DAN PEMASARAN MEDIA SOSIAL - Pusporini Pusporini; Anggi Angga Resti; Tati Handayani (LPPM STIE Muhammadiah Bandung, 2025)
This research aims to explore the potential for innovative transformation that can be achieved by Vera Flower through an integrated approach. Using qualitative methods and SWOT analysis, this research highlights production strengths, possible process improvements, strategic partners, and challenges in facing online competition. The analysis results show that Vera Flower has strengths in a strong vision and mission, marketing innovation and social support, but is also faced with challenges such as limited capital and dependence on certain moments. On the opportunity side, Vera Flower has the potential for partnerships with resellers and digital marketing development. To exploit this potential, Vera Flower can plan strategic steps such as increasing digital marketing, diversifying products, and building partnerships with resellers. With the right strategy, Vera Flower can maximize its growth and success in the online market..